Respon Varietas Unggul Padi Produksi Balitbangtan pada Dua Musim Tanam Berbeda di Provinsi Bali - Anella Retna Kumala Sari; Sagung Ayu Nyoman Aryawati; Nengah Duwijana; I Made Sukarja (Seminar Nasional Lahan Suboptimal, 2020)
Sari ARKS, Aryawati SAN, Duwijana IN, Sukarja IM.  2020.  Response of  superior rice varieties from balitbangtan at different planting season in Bali province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Support of climate and environmental resources affects the introduction and development of superior rice varieties in each region, because not all superior rice varieties have good adaptability in all locations. This study aimed to understand response of superior rice varieties from Balitbangtan namely Inpari 40, Situ Bagendit and Towuti at different planting season in Bali Province. Research was conducted on rainfed land in Subak Babakan Anyar, Tempek Betenan, Mambang Village, Selemadeg Timur District, Tabanan Regency, Bali Province at dry season from April to August 2018 and at rainy season from Desember 2018 to April 2019. Research was arranged by using Compeletely Randomized Design with three replications derived from six treatments namely Inpari 40, Situ Bagendit and Towuti cultivated at dry season and rainy season. Result showed that the different planting season significantly affected on production the dry paddy grain of milling by those varieties. Rice production at rainy season was better than dry season. The highest production was produced by Situ Bagendit followed by Inpari 40 and Towuti at rainy season. Meanwhile, Inpari 40 produced the highest result at dry season compared to others at same planting season. Superior rice varieties of Balitbangtan production namely Inpari 40, Situ Bagendit and Towuti gave response of growth equally both at dry season and rainy season. These superior varieties rice had stable of adaptation ability to growth performance both at dry season and rainy season.